2021
DOI: 10.1002/asl.1041
|View full text |Cite
|
Sign up to set email alerts
|

Changes in snow depth under elevation‐dependent warming over the Tibetan Plateau

Abstract: Snow plays an essential role in regulating climate change, the hydrological cycle, and various biological processes. Passive microwave snow depth data and gridded data from the Climate Research Unit (CRU_TS4.04) are utilized in this study to investigate spatiotemporal variations of snow depth over the Tibetan Plateau (TP), with special focus on the vertical dimension. The response of snow to elevationdependent warming (EDW) is determined accordingly. High mountains experience more rapid warming than lower elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The rapid increase in the number of HW events in the northwestern parts of Pakistan can be attributed to an elevation‐dependent increase in temperature since these areas are located at relatively high altitudes. Several studies have reported more warming in the northwestern parts of SA than in the low‐lying plains areas (Pepin et al., 2015; Shen et al., 2021; You et al., 2020). Interestingly, the Indo‐Pak border is expected to have consistent increases in both the number of daytime and nighttime HWs during 2061–2100, relative to the historical period (1975–2014).…”
Section: Resultsmentioning
confidence: 99%
“…The rapid increase in the number of HW events in the northwestern parts of Pakistan can be attributed to an elevation‐dependent increase in temperature since these areas are located at relatively high altitudes. Several studies have reported more warming in the northwestern parts of SA than in the low‐lying plains areas (Pepin et al., 2015; Shen et al., 2021; You et al., 2020). Interestingly, the Indo‐Pak border is expected to have consistent increases in both the number of daytime and nighttime HWs during 2061–2100, relative to the historical period (1975–2014).…”
Section: Resultsmentioning
confidence: 99%
“…Many recent studies reported good agreement of the GCMs with CRU data over Pakistan and neighbouring countries (Adnan et al ., 2015; Asmat and Athar, 2015; Abbasian et al ., 2018; Das et al ., 2018; Latif et al ., 2018; Ahmed et al ., 2019d; Almazroui et al ., 2020; Ullah et al ., 2020; Guo et al ., 2021; Shen et al ., 2021). Hence, the statistical techniques used in the current study for comparing the historical performance of the GCMs assumed CRU as reference data.…”
Section: Study Area Data and Methodsmentioning
confidence: 99%
“…Particularly, in this study, we observed that zone 2 and zone 3 have an increasing trend of temperature and decreasing trend of rainfall, which is the reason for decreasing trend of SCA (Supplementary Table S4). Annual SCA at mid-altitude zones decreases but insignificantly which is closely related to the elevation-dependent temperature change as compared to precipitation (Misra et al, 2020;Shen et al, 2021) (Supplementary Table S4).…”
Section: Topographic Parameter and Snow Cover Areamentioning
confidence: 99%